2019
DOI: 10.1177/1925362119851113
|View full text |Cite
|
Sign up to set email alerts
|

Placental Abnormalities Associated With Childbirth

Abstract: Pathologists are faced with a variety of problems when considering placental tissue in cases of stillbirth. It is recognized that there are changes which occur following fetal demise and which can complicate the assessment and may coexist with other morphological changes. It is recognized that up to 25% of stillbirths may have a recognizable abnormality causing fetal demise. A systematic review of placental tissue allows many of these disorders to be identified. This review considers macroscopic and microscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This might be explained by the deteriorated maternal condition resulting in vessel compression and cessation of blood flow, as well as fetal perfusion. lastly, the combination of all these effects could lead to fetal asphyxia and death ( 78 , 79 ). In line with this, history of ANC visits, urinary tract infection, being anemic, previous history of cesarean section, gestational hypertension, and diabetes were known modifiable risk factors for both maternal health conditions (i.e., Maternal complication of pregnancy and complications of the placenta, cord, and membranes) ( 30 , 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the deteriorated maternal condition resulting in vessel compression and cessation of blood flow, as well as fetal perfusion. lastly, the combination of all these effects could lead to fetal asphyxia and death ( 78 , 79 ). In line with this, history of ANC visits, urinary tract infection, being anemic, previous history of cesarean section, gestational hypertension, and diabetes were known modifiable risk factors for both maternal health conditions (i.e., Maternal complication of pregnancy and complications of the placenta, cord, and membranes) ( 30 , 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular alterations of the umbilical cord, among other placental or maternal vascular pathologies such as chorioamnionitis, hypertension or preeclampsia [42][43][44] can affect foetal oxygenation during pregnancy. Foetal hypoxia results in anaerobic metabolism in which organic acids such as lactate and ketoacids are produced, leading to metabolic or mixed acidosis.…”
Section: Foetal Programming: How Vascular Alterations In the Umbilica...mentioning
confidence: 99%
“…[1][2][3] Apart from maternal (hypertensive disorders of pregnancy, diabetes mellitus, infection), and fetal (fetal growth restriction, fetal structural abnormalities, umbilical cord abnormalities) conditions, placental (maternal and fetal vascular malperfusion, inflammation) abnormalities are commonly known to cause stillbirth. [4][5][6][7][8][9][10] Although having a history of abnormal pregnancy is considered a strong risk factor for stillbirth, 11,12 one study 2 reported that one third of the stillbirths occurred in women who had an apparently healthy pregnancy. Because they are related to labor and delivery problems, intrapartum stillbirths usually have no antenatal risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Stillbirth defined as fetal death in utero at ≥20 weeks of gestation accounts for approximately 60% of all perinatal deaths; however, its cause remains unknown in 25%–60% of all cases 1–3 . Apart from maternal (hypertensive disorders of pregnancy, diabetes mellitus, infection), and fetal (fetal growth restriction, fetal structural abnormalities, umbilical cord abnormalities) conditions, placental (maternal and fetal vascular malperfusion, inflammation) abnormalities are commonly known to cause stillbirth 4–10 . Although having a history of abnormal pregnancy is considered a strong risk factor for stillbirth, 11,12 one study 2 reported that one third of the stillbirths occurred in women who had an apparently healthy pregnancy.…”
Section: Introductionmentioning
confidence: 99%